Anchoring cobalt single atoms on 2D covalent triazine framework with charge nanospatial separation for enhanced photocatalytic pollution degradation. (June 2022) - Chen, J.; Li, G.; Lu, N.; Lin, H.; Zhou, S.; Liu, F.
Abstract: Covalent triazine frameworks (CTFs) show great potential in photocatalytic fields, while their practical efficiency is still limited due to rapid charge recombination. Here we report a nanospatial separation strategy for photoinduced electron-hole pairs of CTF-1 nanosheets via single-atom Co using facile pyrolysis and phosphorization to form stable Co–N3 (≈1.60 Å) architecture. HAADF-STEM image demonstrates Co atoms are uniformly dispersed onto ultrathin CTF-1. The local structure surrounding and chemical valent state of Co are systematically investigated by Fourier-transformed EXAFS and K-edge XANES, respectively. Co single atoms as oxidation centers can capture holes transferred from CTF-1, thus resulting in narrow bandgap and improved photo-exciton dissociation in the two-dimensional (2D) direction. The obtained Co/CTF-1 exhibits excellent efficiency of 99.9% for pollutant photodegradation, far outperforming that of pristine CTF-1 (68.8%). Nanospatial separation endows Co/CTF-1 with various micropollution removal capabilities, outstanding cyclic stability, and a widely effective pH range (1.0–11.0) under visible light. Furthermore, active oxidating radicals of h + and O2 − are dominant in photocatalytic degradation for various organic contaminants. This study motivates the atomic design and fabrication of 2D photocatalysts with excellent charge nanospatial separation. Graphical abstract: Image 1 Highlights: We synthesize Co/CTF-1 photocatalysts via pyrolysis and phosphorization. Co single atoms are uniformly anchored onto the 2D CTF-1 framework to form stable Co–N3 architecture. Co atoms as oxidation centers can capture holes to improve charge nanospatial separation. Co/CTF-1 enhances photocatalytic pollution degradation efficiency compared to CTF-1 counterparts. Co/CTF-1 exhibits outstanding cyclic stability and a widely effective pH range (1.0–11.0).